Brief for Consultations with the Secrétariat aux relations avec les Québécois d’expression anglaise - Seniors Action Quebec (SAQ) (2024)

Seniors Action Quebec E-Newsletter - Seniors Action Quebec (SAQ) (2023)

E-Newsletter - Seniors Action Quebec (2023)

Seniors Action Quebec Presentation on Study Matters Relating to Minority-Language Health Services - Seniors Action Quebec (SAQ) (2023)

Seniors Action Quebec Brief : Vieillir et vivre ensemble, chez soi, dans sa communauté, au Québec (VVE) - Plan d’action 2024-2029 - Seniors Action Quebec (SAQ) (2023)

E-Newsletter - Seniors Action Quebec (2023)

Annual Report 2022-2023 - Seniors Action Quebec (SAQ) (2023)

Rapport annuel 2022-2023 - Seniors Action Quebec (SAQ) (2023)

E-Newsletter - Seniors Action Quebec (SAQ) (2022)

E-Newsletter - Seniors Action Quebec (SAQ) (2022)

Seniors Action Quebec Welcomes Additional Support for Seniors and for the English-speaking Community Announced in Quebec Budget - Seniors Action Quebec (SAQ) (2022)

2021-2022 : Annual Report / Rapport annuel - Seniors Action Quebec (SAQ) (2022)

E-Newsletter - Seniors Action Quebec (SAQ) (2021)

Press Release : A Celebration in Song, Spoken Word & Step Final Episode of We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Making Homemade Tomato Sauce with Greg on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Author Conversations with Richard King on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Organic Gardening with Hannah on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

E-Newsletter - Seniors Action Quebec (SAQ) (2021)

Press Release : Urban Art with Jamie on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Tango Dancing with Mireille & Friends on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Making Jam with Susan on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : The Flamboyant World of Drag with Barbada on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Community Organization of Lanaudière (ECOL) (2021)

E-Newsletter - Seniors Action Quebec (SAQ) (2021)

Press Release : Wine Pairing with Ana on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Horse Therapy with Karine on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Indigenous Hoop Dancing with Makhena on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Bird Watching with Joël Coutu on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Eating Healthy on a Budget with Crystal on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Animal Fostering with Cindy on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Spring Special! Gardening in Small Spaces on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Flower Arranging on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Laughter Yoga on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

E-Newsletter - Seniors Action Quebec (SAQ) (2021)

Press Release : New Episode of Web Series for Seniors We’re All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : New York Times Bestselling Author Louise Penny Is The Guest of the Web Series for Seniors We’re All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Celebrated New York Times Bestselling Author Louise Penny, on Senior’s Web Series We’re All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

2020/2021 Annual Report - Seniors Action Quebec (SAQ) (2021)

Press Release : A Holiday Concert of Quebec Performers at Martha Wainwright's URSA Follows Incredibly Popular First Episode of "We're All In This Together" - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2020)

Press Release : Launch of Project We Are All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2020)

E-Newsletter - Seniors Action Quebec (SAQ) (2020)

Newsletter - Seniors Action Quebec (SAQ) (2020)

Deconfinement Guidelines : What You Should Know in Times of Crisis - Seniors Action Quebec (SAQ) (2020)

Newsletter - Seniors Action Quebec (SAQ) (2020)

Seniors Action Quebec Statement on Situation at Residence Herron - Seniors Action Quebec (SAQ) (2020)

Covid-19 : Considerations When Deciding to Move Seniors from Residences or CHSLDS - Seniors Action Quebec (SAQ) (2020)

Questions Pertinentes à poser à une résidence pour aînes pendant la pandémie de Covid-19 - Seniors Action Quebec (SAQ) (2020)

Tips on Helping Seniors Deal with Isolation During Covid-19 Pandemic - Seniors Action Quebec (SAQ) (2020)

What to Ask a Senior's Residence During the Covid-19 Pandemic - Seniors Action Quebec (SAQ) (2020)

9 Quick Safety Tips to Manage Your Medications - Trimble, Johanna; Currie, Janet (2018)

Mieux gérer vos médicaments : 9 conseils utiles - Trimble, Johanna; Currie, Janet (2018)

Building Community Capacity From Evidence to Action (2015-2016) - Pocock, Joanne (2016)

Focus Group Findings 2015-2016 - Seniors Action Quebec (SAQ) (2016)

Building Community Capacity From Evidence to Action (2015-2016) : Profile of English-speaking Seniors : CLSC Manicouagan - Pocock, Joanne (Seniors Action Quebec (SAQ), 2015)
The Seniors Action Québec (SAQ) project is designed to mobilize English-speaking (ES) seniors (65+) and their communities in four regions of the province (Gaspésie, Greater Quebec City, Outaouais and the North Shore). This will be done by creating a network among English language regional community organizations to amplify the voice of minority language seniors and enhance their contribution to the vitality of their communities. The project will ready the network to identify critical issues affecting English-speaking seniors, establish regional action plans to address seniors’ priorities and to generally promote awareness of provincial and regional organizations serving the interests of the 65 years and over age group.

Building Community Capacity From Evidence to Action (2015-2016) : Profile of English-speaking Seniors : CLSC Territoire Naskapi - Pocock, Joanne (Seniors Action Quebec (SAQ), 2015)
The Seniors Action Québec (SAQ) project is designed to mobilize English-speaking (ES) seniors (65+) and their communities in four regions of the province (Gaspésie, Greater Quebec City, Outaouais and the North Shore). This will be done by creating a network among English language regional community organizations to amplify the voice of minority language seniors and enhance their contribution to the vitality of their communities. The project will ready the network to identify critical issues affecting English-speaking seniors, establish regional action plans to address seniors’ priorities and to generally promote awareness of provincial and regional organizations serving the interests of the 65 years and over age group.

Building Community Capacity From Evidence to Action (2015-2016) : Profile of English-speaking Seniors : CSSS de La Côte-de-Gaspé - Pocock, Joanne (Seniors Action Quebec (SAQ), 2015)
The Seniors Action Québec (SAQ) project is designed to mobilize English-speaking (ES) seniors (65+) and their communities in four regions of the province (Gaspésie, Greater Quebec City, Outaouais and the North Shore). This will be done by creating a network among English language regional community organizations to amplify the voice of minority language seniors and enhance their contribution to the vitality of their communities. The project will ready the network to identify critical issues affecting English-speaking seniors, establish regional action plans to address seniors’ priorities and to generally promote awareness of provincial and regional organizations serving the interests of the 65 years and over age group.

Building Community Capacity From Evidence to Action (2015-2016) : Profile of English-speaking Seniors : Rocher-Percé - Pocock, Joanne (Seniors Action Quebec (SAQ), 2015)
The Seniors Action Québec (SAQ) project is designed to mobilize English-speaking (ES) seniors (65+) and their communities in four regions of the province (Gaspésie, Greater Quebec City, Outaouais and the North Shore). This will be done by creating a network among English language regional community organizations to amplify the voice of minority language seniors and enhance their contribution to the vitality of their communities. The project will ready the network to identify critical issues affecting English-speaking seniors, establish regional action plans to address seniors’ priorities and to generally promote awareness of provincial and regional organizations serving the interests of the 65 years and over age group.

Building Communities Together : Laurentians, Outaouais, Quebec Region - Seniors Action Quebec (SAQ) (2014)

Covid-19 : Facteurs déterminants à considérer avant de décider de transférer un aîné d'une résidence ou d'un CHSLD - Seniors Action Quebec (SAQ)

Isolement des aînés et pandémie de Covid-19 - Seniors Action Quebec (SAQ)